(untitled) (Nigerian Journal of Physiological Sciences, 2021)
In this study, the effects of maternal exposure to Bonny Light Crude Oil (BLCO) on reproductive functions of the offspring was investigated in Wistar rats. Ten pregnant rats were divided into two groups (n=5). Group 1 served as the control, it was administered 0.75ml/Kg bwt/day normal saline and Group 2 was administered 0.75ml/Kg bwt/day BLCO. Serum hormonal profile, sperm indices, estrous cycle length and pubertal timing were assessed as measures of reproductive function. Tissue Malondialdehyde, Catalase and SOD activities were assessed as indices of oxidative stress. Results obtained showed that BLCO significantly (p<0.05) reduced birth weight, anogenital distance (AGD) at birth, sperm count, motility and normal morphology, serum testosterone, testicular and epididymal SOD and catalase activities in the male offsprings. However, days of preputial separation, relative weight of testis and epididymis, testicular and epididymal MDA were significantly (p<0.05) raised by gestational exposure to BLCO. In the female offspring, birth weight, AGD at birth, relative weight of ovaries and uterus, SOD, catalase activities, serum LH were significantly reduced by BLCO exposure during gestation. Moreover, uterine and testicular MDA, serum estradiol and FSH were significantly increased by BLCO treatment during gestation. In conclusion, maternal exposure to BLCO during gestation may alter reproductive indices in the offspring and increased occurrence of oxidative stress in reproductive structures in male and female offspring of Wistar rats.